INTEGRASI LAYANAN FINTECH DALAM PLATFORM E-COMMERCE: STUDI KASUS PENGGUNAAN PAYLATER PADA GENERASI Z - Muzakkir, Muzakkir; Azisah Syam, Nur; Fatwa, Syafira (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
The rapid development of Financial Technology (Fintech) services within e-commerce platforms has given rise to various alternative payment methods, notably Paylater, which is increasingly popular among Indonesia's Generation Z. This study aims to analyze the integration of Paylater services in e-commerce, evaluating the driving factors for adoption, risk awareness, and security perceptions from the perspective of Generation Z users in Indonesia. Employing an exploratory qualitative approach through a comprehensive literature review and an online survey of 12 Generation Z respondents, data were descriptively analyzed to delineate usage patterns and service perceptions. Findings indicate that 0% installment promotions, payment flexibility, and easy access are primary drivers of Paylater adoption. While most respondents are aware of additional fees, only a minority fully comprehend the detailed calculations, highlighting a digital financial literacy gap. Service satisfaction levels are notably high, yet security perceptions remain neutral, and personal financial management capabilities are rated as